THE EFFECT OF LEADPRENEURSHIP AND COMPETENCE ON EMPLOYEE PERFORMANCE (SURVEY STUDY PT. JASA DAN KEPARIWISATAAN JAWA BARAT, TOUR AND TRAVEL UNIT) - Andityo Wahyu Juniarsyah; Sri Rochani Mulyani; Kosasih; Farida Yuliaty; Vip Paramarta; Fitriana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
PT. Jaswita Jabar, which is a Regionally-Owned Enterprise (BUMD) engaged in tourism, property and business services. PT. Jaswita Jabar has a vision to become the largest and most trusted property and tourism company in West Java in 2025. To achieve this vision, it is necessary to have a planned and structured business management so that PT. Jaswita Jabar is ready to compete in an increasingly competitive industrial world. The method used in this study is a quantitative approach, with descriptive and verification analysis. The research sample is employees in the PT. Jaswita Jabar environment. The results of the study using multiple linear regression analysis, obtained a regression equation model Y = a + 0.835X1 + 0.606X2, showing a positive direction coefficient, meaning that every change in leadpreneurship and competence will improve employee performance. While the results of the hypothesis test show a significant influence of leadpreneurship and competence on employee performance both partially and simultaneously, where the p-value.